POTENSI TEH DAUN SUNGKAI (PERONEMA CANESCENS JACK) TERHADAP PENURUNAN TEKANAN DARAH DAN KADAR MALONDIALDEHYDE (MDA) - Utami, Umi Juarna; Sumarni, Sri; Maigoda, Tonny Cortis (Poltekkes Kemenkes Bandung, 2025)
Hypertension as the silent killer, one of the main factors causing death in the world. Hypertension among women is higher (34.7%) than men (26.9%). Hypertension in Women of Childbearing Age (WCA) cause’s of pregnancy complications. Nonpharmacological therapy using sungkai leaves rich in flavonoids as alternative antihypertensive and lowers MDA levels.The study aimed to evaluate that giving sungkai leaf tea has potential to reduce blood pressure and Malondialdehyde levels in hypertensive WCA. This research was quasy experimental pre-test and post-test with control group design. The population was WCA grade 1 hypertension in ​​the Nusa Indah Health Center, Bengkulu City. The sample was 30 people with purposive sampling technique, 15 in intervention group were given sungkai leaf tea dose of 2gr twice/day and amlodipine 5mg/day and 15 in control group given amlodipine 5mg/day for 7 days of research. The results of the paired sample t-test statistical showed difference in the average decrease in systolic blood pressure at intervention group by 28.67 mmHg compared to control group by 18.33 mmHg. Diastolic blood pressure decreased significantly with average of 11.80 mmHg in intervention group compared control group is 7.20 mmHg. MDA levels in intervention group decreased by 1.65 nmol/ml, then control group by 1.02 nmol/ml. The Independent t-test showed that intervention results in the sungkai leaf tea group were more effective than the control group with p-value 0.000 <0.05. These results has proven the potential of sungkai leaf tea to be effective as blood pressure lowering agent and MDA levels in hypertensive WCA.